Penatalaksanaan Fisioterapi Pada Bell's Palsy Sinistra Di Rsud Sragen - Rahmawati, Annisa Nur, Wahyuni, SSt. FT. M.Kes (2016)
Background: Bell's palsy is a disorder of the facial nerve that causes weakness or paralysis of the muscles abruptly on one side of the face. In the case of bell's palsy, physiotherapy role is to prevent further complications. Physiotherapy intervention technologies that can be used in case of bell's palsy varies, some of which are infra red, electrical stimulation, massage, and mirror exercise. Objective: To determine the benefits of infra red, electrical stimulation, massage, and mirror exercise in increasing the strength of the facial muscles and improve functional ability of facial muscles in patients bell's palsy. Results: After 6 times act with infra red, electrical stimulation, massage, and mirror exercise, the results of strength measurement of facial muscles using MMT as follows: (a) m. occipitofrontalis T1: 0 become T6: 1, (b) m. corrugator supercili T1: 0 become T6: 1, (c) m. procerus T1: 0 become T6: 1, (d) m. orbicularis oculi T1: 0 become T6: 3, (e) m. nasalis T1: 0 become T6: 1, (f) m. anguli oris depressor T1: 0 become T6: 1, (g) m. zigomaticum T1: 0 become T6: 1, (h) m. orbicularis oris T1: 0 become T6: 1, (i) m. buccinators T1: 0 become T6: 1, and (j) m. mentalist T1: 3 to T6: 5. While the results of measurement of the ability of functional activity using Ugo Fisch Scale as follows: (a) break T1: 0 become T6: 30, (b) frown T1: 0 become T6: 30, (c) a close eye T1: 0 become T6: 70, (d) smiling T1: 0 become T6: 30, and (e) whistling T1: 0 become T6: 30. Conclusion: The provision of intervention by infra Red, electrical stimulation, massage, and mirror exercise can be beneficial to increase the strength of muscles of the face and the ability of the functional activity of the facial muscles in bell's palsy. Keywords: Bell's Palsy, Infra Red, Massage, Electrical Stimulation, Mirror Exercise.